Mushrooms as a source of compounds that induce programmed cell death in tumour cells - Reis, Filipa S. (2018)
One of the hallmarks of cancer is the ability of tumour cells to resist cell death. Consequently, therapies based on the induction of programmed cell death (PCD) constitute an area of scientific interest. Mushrooms are a demonstrated source of extracts and compounds with antitumour properties. One of such properties is the capacity to induce PCD. This chapter reviews the existing evidence of mushroom extracts inducing apoptosis or autophagy in human tumour cell lines and focuses on the identified compounds that are responsible for those cellular activities including the known pathways involved. This chapter is intended to identify the most bioactive classes of compounds and the cell lines in which they exert their activity. This information aims to present the basis for future works, in order to obtain or create new therapies for the treatment of cancer, including pharmaceutical and/or nutraceutical products.